Mitochondrial DNA damage in HIV infection: a mechanistic driver of immunometabolic dysfunction and chronic inflammation - Ma, Li; Wang, Xiaolei; Xu, Huanbin (Frontiers in Immunology, 2026)
Mitochondria are central regulators of cellular metabolism and immunity. Human immunodeficiency virus (HIV) infection and antiretroviral therapy (ART) are associated with metabolic complications and chronic inflammation, yet the underlying mechanisms remain incompletely understood. Increasing evidence implicates mitochondrial dysfunction—particularly mitochondrial DNA (mtDNA) damage—as a key contributor. HIV/SIV infection and ART both compromise mtDNA integrity through direct and indirect mechanisms, leading to impaired oxidative phosphorylation, dysregulated reactive oxygen species, and altered mitochondrial dynamics. These changes contribute to immune cell bioenergetic failure, T cell exhaustion, and cytosolic release of mtDNA, which can activate cGAS-STING and NLRP3 pathways to sustain chronic inflammation. In addition, certain ART drugs, especially early nucleoside reverse transcriptase inhibitors, inhibit polymerase γ, driving mtDNA depletion and mutation accumulation that underlie toxicities such as lipodystrophy, neuropathy, and accelerated aging. Monitoring mtDNA copy number and mutational burden may offer useful biomarkers of immune recovery and treatment-related complications. Targeting mitochondrial protection and repair represents a promising strategy to improve long-term outcomes in people living with HIV.